Strategies that facilitated expansion of a postgraduate year 1 pharmacy residency program across a community hospital–based health system. (15th March 2017) - Ticcioni, Andrew; Erdman, Diane; Scott, Benjamin; Gillard, Mike; Cai, Lijian
Abstract: Purpose: Seven strategies used to expand an existing postgraduate year 1 (PGY1) pharmacy residency program and launch 3 new PGY1 residency programs in a multisite community hospital–based health system are described. Summary: The vision of ASHP and other pharmacy organizations of providing advanced training (e.g., residency training) to all pharmacists who plan to be involved in direct patient care has not yet been realized, and the capacity to provide such training has not kept pace with the demand. Wheaton Franciscan Healthcare (WFH) leaders expanded PGY1 residency training and recognized 7 strategies that enabled program growth at multiple sites within the healthcare system. WFH pharmacy leaders were charged to (1) take a bold approach to expansion of residency training, (2) place the residency program at the center of pharmacy department operations, (3) develop teams of high-performing preceptors, (4) partner with schools of pharmacy, (5) initiate rotations at other facilities within the healthcare system, (6) elevate resident ownership of and engagement in the residency program, and (7) enhance communication and collaboration across the program. As a result of these strategies, a single residency program with 2 residents was expanded in a 4-year time frame to encompass 4 programs with a total of 14 residents. Conclusion: Seven strategies facilitated the expansion of 1 pharmacy residency program and the successful launch of 3 new PGY1 residency programs across the WFH system. These strategies provide a basic framework for both residency training expansion and clinical service development.